Abandono afetivo: reflexos no desenvolvimento das crianças e sua indenizabilidade - Jank, Pedro Arthur (2024)
The present study aims to analyze the possibility of applying Civil Liability in cases involving the emotional abandonment of minor children by their parents. To this end, an analysis is made of the importance of affection in family ties today. It is also intended to investigate the possible consequences of abandonment on the physical and emotional development of minors and question whether the legal system is capable of finding solutions capable of remedying these damages. As for the methodology, this work was based on a bibliographical review that included doctrine, scientific articles and jurisprudence. Furthermore, the deductive method was used, based on the analysis of recent decisions of the Superior Court of Justice to clarify how jurisprudence has treated the conduct of parents who emotionally abandon their children. It was concluded that judges are moving towards understanding that compensation resulting from emotional abandonment is appropriate, understanding that the reintegration of family ties, mainly through the institute of mediation, can be a more appropriate means of alleviating the suffering of the abandoned person.